Integration of Character Education Values in Islamic Religious Education Learning at Madrasah Tsanawiyah Al-Fadliliyah Darussalam Ciamis - Didih Syakir Munandar; Dodo Suhada; Uus Ruswandi; Bambang Samsul Arifin (Edumaspul: Jurnal Pendidikan, 2022)
Education to revive character is one of the alternative answers to renew the aridity of our educational output. This spirit of value education must be internalized in all components of education so as to create educational outputs that have a balance of competencies both on the cognitive, affective and psychomotor planes. This research was conducted to reveal student character through the integration of character values in PAI learning which was implemented at MTs Al-Fadliyah Darussalam Ciamis. The method used is descriptive qualitative analysis, with data collection carried out by observation supplemented by interviews and documentation. The results of the study show that MTs Al-Fadliliyah Darussalam Ciamis integrates character (religious, honest, independent, communicative, responsible and democratic and etc) in PAI learning which is carried out with special emphasis on material, methods and is supported by several madrasah programs. In general, the integration of character values in PAI learning runs effectively, because it is supported by sufficient facilities at MTs Al-Fadliliyah Darussalam Ciamis.